Heat Transfer From a 2D Backward Facing Step With Isotropic Porous Floor Segments - A/K Abu-Hijleh, Bassam (2000)
The incompressible laminar reattaching flow over a 2D backward facing step with porous floor segments of different lengths was solved numerically using the finite element method. The focus of this study was the change in the forced convection heat transfer characteristics of the flow field due to the addition of porous floor segments. Several isotropic porous floor segment configurations with different lengths and depths were studied. The porosity of the segments was varied over a wide range by changing the value of the pressure loss coefficient . The changes in the local and overall Nusselt number are reported and discussed. Depending on the configuration, axial variation of the local Nusselt number could be altered. For all configurations, the overall Nusselt number decreased by as much as 16% while the maximum local Nusselt number increased by as much as 170%, both relative to their respective values for the reference case of a solid floor.